Effect of the professional skepticism characteristics of the auditor on audit qualit - الطائي, بشرى فاضل; عثمان, علاء الدين عبد الرحمن (Journal of Economics and Administrative Sciences, 2025)
The professional skepticism is one of the fundamental concepts necessary for practicing the audit profession, without which the auditor can not reach a reasonable assurance as to the correctness of the evidence and the information obtained by the auditing department. The auditor's possession of the characteristics of professional skepticism and his practice of professional skepticism during the audit process lead to an increase The quality of audit and thus raise the confidence of the financial community in the audit profession again after the exposure of several crises led to the loss of financial society confidence in the audit profession.The aim of the study is to measure the impact of professional skepticism on audit quality in Iraqi audit firms and offices, as well as to measure the characteristics of professional skepticism in the Iraqi audit companies and offices through a questionnaire distributed to a sample of auditors in the audit firms and audit offices in Iraq. (62) form. The effect of the variables was shown through the use of statistical models in the form of the lower squares and linear regression model. After testing the hypotheses, a set of conclusions was reached. The impact of professional skepticism on the audit quality of audit firms and audit offices in Iraq is significant. The practice of professional skepticism  leads to an increase in the quality of the audit process by detecting the material errors resulting from fraud or errors, which leads to the confidence of the financial community The research recommended that the legislative and regulatory bodies in Iraq should emphasize the importance of professional skepticism and the need for auditors to exercise professional skepticism during the implementation of the audit process, which leads to increased audit quality.